Administrative Jurisdiction in Ukraine: Discourse Analysis - Smokovych, Mykhailo I. (International Journal of Criminology and Sociology, 2021)
The development of administrative jurisdiction is extremely important for the establishment of a democratic society and the protection of human rights. The purpose of this paper was to study the system of administrative courts in Ukraine and other countries and delineate the powers of courts of different jurisdictions, as well as to study the history of the system of administrative courts in different countries and compare the experience of administrative jurisdictions in different countries. The methodological framework comprised discourse analysis as a method of qualitative research of the issues under consideration. This method involves the study of textual sources, mainly when it comes to understanding law and social laws, as well as their history. In the course of the study, the systems of construction of administrative proceedings of the leading European countries are considered, based on which the general systems of organisation of administrative jurisdiction are outlined: 1) French; 2) German; 3) the common law system; 4) different types of mixed systems. As a result of the research it was established that in general the development of administrative jurisdiction in Ukraine from the 19th century to the present has passed 5 stages and each of them was described. It is stated that the current system of administrative jurisdiction in Ukraine is quite progressive and balanced: administrative courts are a separate three-tier system, and a special procedure has been introduced for administrative cases.